2022
DOI: 10.1002/smmd.20220017
|View full text |Cite
|
Sign up to set email alerts
|

Current treatments after spinal cord injury: Cell engineering, tissue engineering, and combined therapies

Abstract: Both traumatic and non‐traumatic spinal cord injuries (SCIs) can be categorized as damages done to our central nervous system (CNS). The patients' physical and mental health may suffer greatly because of traumatic SCI. With the widespread use of motor vehicles and increasingly aged population, the occurrence of SCI is more frequent than before, creating a considerable burden to global public health. The regeneration process of the spinal cord is hampered by a series of events that occur following SCI like edem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 165 publications
(190 reference statements)
0
9
0
Order By: Relevance
“…53 Ascribed to good flexibility, high water content and cross-linked network structures, hydrogels are expected to be connected with soft neural tissues, realizing soft interaction between human and electronic devices to overcome the mechanical mismatch problem of traditional electronic devices. 54,[64][65][66] More recently, Madden et al discussed the piezoelectric mechanism of piezoelectric F I G U R E 2 Multifunctional BT nanomaterials. (A) Fourier transform infrared spectra (i), transmission electron microscope image (ii), energy dispersive X-ray spectroscopy mapping results (iii, iv) of PMMA@BTNWs.…”
Section: Organic Piezoelectric Polymersmentioning
confidence: 99%
See 1 more Smart Citation
“…53 Ascribed to good flexibility, high water content and cross-linked network structures, hydrogels are expected to be connected with soft neural tissues, realizing soft interaction between human and electronic devices to overcome the mechanical mismatch problem of traditional electronic devices. 54,[64][65][66] More recently, Madden et al discussed the piezoelectric mechanism of piezoelectric F I G U R E 2 Multifunctional BT nanomaterials. (A) Fourier transform infrared spectra (i), transmission electron microscope image (ii), energy dispersive X-ray spectroscopy mapping results (iii, iv) of PMMA@BTNWs.…”
Section: Organic Piezoelectric Polymersmentioning
confidence: 99%
“…Ascribed to good flexibility, high water content and cross‐linked network structures, hydrogels are expected to be connected with soft neural tissues, realizing soft interaction between human and electronic devices to overcome the mechanical mismatch problem of traditional electronic devices 54,64–66 . More recently, Madden et al.…”
Section: Classification Of Piezoelectric Biomaterialsmentioning
confidence: 99%
“…92 Recently, scaffolds for guiding neural behaviors have been constructed using various biomaterials to promote nerve regeneration. [93][94][95][96] Hu et al reported a conductive and anisotropic substrate by assembling superaligned carbon-nanotube sheets (SA-CNTs) onto biocompatible GelMA hydrogel (GelMA-ACNT) (Figure 8A). 97 The composite substrate inherited the conductivity and topological morphology of SA-CNTs and the good cytocompatibility of GelMA hydrogel.…”
Section: Bionic Scaffoldsmentioning
confidence: 99%
“…The apoptosis and degeneration of SGNs can directly lead to the impairment of the auditory pathway, resulting in serious hearing disorders, and the directed regeneration of SGNs has exhibited promise in the treatment of hearing loss 92 . Recently, scaffolds for guiding neural behaviors have been constructed using various biomaterials to promote nerve regeneration 93–96 . Hu et al.…”
Section: Biomedical Engineering Technologies For Hearing Reconstructionmentioning
confidence: 99%
“…Still, almost three million people worldwide suffer from SCI, with tragic personal and social consequences and high financial costs (more than four billion dollars annually). 1–3 Cascade interactions such as cystic cavitation, generation of glial scar, and the aggregation of inhibitors associated with myelin appear in the SCI lesion site microenvironment during the acute process. 4 By completing the process of glial scar formation, functional nerve recovery leads to failure in nervous tissue regeneration and movement restoration.…”
Section: Introductionmentioning
confidence: 99%